"Signs of Suicide" Shows Promise as a Middle School Suicide Prevention Program. Issue 6 (2nd May 2014) - Schilling, Elizabeth A.; Lawless, Martha; Buchanan, Laurel; Aseltine, Robert H.
<x xml:space="preserve">Abstract</x> Although the Signs of Suicide (SOS) suicide prevention program has been implemented at both the middle and high school levels, its efficacy has been demonstrated previously only among high school students. The current study evaluated SOS implemented in high military impact middle schools. Compared to controls, SOS participants demonstrated improved knowledge about suicide and suicide prevention, and participants with pretest ideation reported fewer suicidal behaviors at posttest than controls with pretest ideation. These results provide preliminary evidence for SOS's efficacy as a suicide prevention program for middle school students.